Understanding the social dimensions of kidney care pathways: A scoping review protocol - Reindolf Anokye; James Larkin; Abass Fehintola; Jessica Eustace-Cook; Rodrigo Martínez-Cadenas; Brett Duane; Bridget Johnston (PLoS ONE, 2025)
Objective This scoping review aims to map the social dimensions of kidney care pathways. Introduction End-stage kidney disease places significant demands on patients, caregivers, healthcare professionals, and the broader healthcare system. Kidney replacement therapy and conservative kidney management are the common management pathways for end stage kidney disease, but its delivery entails substantial time, financial, and social costs. Research has documented some social aspects of kidney care pathways, but findings are fragmented across disciplines and have not been synthesised coherently. A scoping review is therefore needed to map the existing evidence, identify key domains of social impact, and highlight gaps to inform future research and policy. Method Eligible studies will include primary research that reports on the social dimensions of managing end-stage kidney disease (ESKD) in adults. Studies from all settings, involving relevant stakeholder groups including patients with end stage kidney disease, informal caregivers, healthcare staff, and Industrial and supply chain workers engaged in different roles associated with kidney replacement therapy and/or conservative kidney management, will be included. The review will follow JBI methodology. Peer-reviewed and grey literature will be identified through searches of electronic databases (MEDLINE, CINAHL, PsycInfo, SocINDEX, EconLit, Web of Science) and grey literature sources (including Google Scholar and organisational reports). Reference lists of relevant reviews and identified articles will also be screened to identify any other relevant articles. Two reviewers will independently screen records and extract data using a predefined form. Results will be synthesised narratively and presented in thematic and tabular formats. Discussion This scoping review aims to generate evidence on the social impact of kidney replacement therapy and conservative management across multiple stakeholder groups. The review will provide a structured overview of how social outcomes are conceptualised, measured, and reported across the kidney care continuum. Review registration Open Science Framework osf.io/63wpk.